AL JAZEERA’S ROLE IN THE ENFORCEMENT OF INTERNATIONAL HUMANITARIAN LAW IN THE CASE OF SHOOTING JOURNALIST SHIREEN ABU AKLEH BY ISRAELI ARMY - Faizatuz Zuhroh (Mediasi: Journal of International Relations, 2022)
This research is present to analyze through the concept of the international community implemented in the case study. The concept of the international community is used to analyze the role played in the process of enforcing international law. The killing of journalists in armed conflict areas always ends with impunity for the perpetrators. To overcome this, Al Jazeera performs its role as an international community through its three functions: propaganda function, social control function and advocacy function. In carrying out its propaganda and social control functions, Al Jazeera continues to voice the implementation of investigations through news about the Shireen Abu Akleh shooting case, causing many solidarity actions and campaigns in response to this and the investigation as a response from the government and related institutions. Then in carrying out its advocacy function, Al Jazeera submitted the Shireen Abu Akleh shooting case to the International Criminal Court (ICC) after the collection of evidence obtained from investigations conducted by many parties. The research method used is descriptive qualitative method. The results of this study, that Al Jazeera as an international community has succeeded in carrying out its role in international law enforcement efforts carried out through three functions it has as an international media organization.